Enhancing logical thinking among computer science students through cooperative learning / Mahfudzah Othman, Fazlin Marini Hussain and Khairunisa Nikman - Othman, Mahfudzah; Hussain, Fazlin Marini; Nikman, Khairunisa (Universiti Teknologi MARA Cawangan Pahang, 2010)
This study is aimed to investigate the logical thinking levels among first semester students who enrolled in the introductory programming course in Computer Science studies. A selected group of ninety-seven students were asked to take the Group Assessment Logical Thinking (GALT) tests in the beginning and at the end of the semester. The results derived from the GALT pre-tests will be used to divide the students into learning groups, where each group consists of two High Logical thinkers (HLT) and two Low Logical thinkers (LLT). Afterwards, the Cooperative Learning (CL) method which is named Numbered Heads Together is then introduced in the programming classes. Later, at the end of the semester, the GALT post-test results are then being compared with the pre-test results to see the changes of logical thinking levels among the students. The results have shown an increasing number of students with HLT levels. Due to the effectiveness of practicing CL method in classes, a proposed framework for an online collaborative learning system is also being discussed in this paper. Another technique called Think-Pair- Share is being selected to suit the virtual environment. It is hoped that the cooperative learning methods whether the in-class practice or online collaboration will be seen as an innovative way to enhance the students’ logical thinking levels thus improving their performances in programming courses.